Proposal of a Mission Management Module for Embedded Agent Systems - Nazarov, Georgiy C. Tanca; Silvestre, Iago; Santos, Fernando R.; Hübner, Jomi F.; Becker, Leandro Buss (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2025)
Multiagent Systems have characteristics suitable to be used in the control of Multi-Robot Systems (MRS), but due to the different missions that can be performed in an application, and the complex interactions among them, some difficulties are observed in their implementation. Therefore, we propose a Mission Management Module (MMM), to be used in Embedded Agent Systems, that is capable of switching between missions as required, while keeping track of mission progress, preventing task repetition when returning to a previously interrupted mission. To design this proposal, we define key concepts and requirements to assist and delimit the scope of this module. In addition, we propose a general architecture of a system, within which the MMM is encapsulated, to be used in MRS applications. An initial implementation of the MMM in Jason Language is presented. Finally, we assess this initial implementation and suggest further improvements in order to comply with the proposed requirements.